Lectotypication of Acroporium hyalinum (Reinw. ex Schwägr.) Mitt. (Hypnales: Sematophyllaceae). - Chua, Mung Seng; Ho, Boon Chuan; Monica Suleiman; Qin Zuo; Dian, Xing Zhang; Li Zhang (2018)
Acroporium hyalinum (Reinw. ex Schwägr.) Mitt., an older name for Acroporium stramineum (Reinw. & Hornsch.) M.Fleisch., is applied here in accordance with the principle of nomenclatural priority. Acroporium hyalinum is broadly circumscribed by its erect-spreading, ovate-lanceolate leaves with short acuminate tips. Its infra-speci¬c delimitation, however, has not been clearly resolved. Based on careful examination of nearly 200 specimens, including 35 types associated with A. hyalinum and its synonyms, all the three varieties proposed by Tan (1994) are accepted here as Acroporium hyalinum (Reinw. ex Schwägr.) Mitt. var. hyalinum,A. hyalinum var. hamulatum (M.Fleisch.) M.S.Chua & B.C.Ho, and A. hyalinum var. turgidum (M.Fleisch.) M.S.Chua & B.C.Ho, the latter two names being new combinations. Descriptions and an identi¬cation key of these three varieties are provided, along with taxonomic notes and illustrations. Lectotypi¬cation of Hypnum hyalinum Reinw. & Hornsch. is proposed.